NOAH: NMR supersequences for small molecule analysis and structure elucidation - Kupče, Ē; Claridge, T (Wiley, 2017)
Nested NMR experiments combining up to five conventional NMR pulse sequences into one supersequence are introduced. The core two-dimensional NMR techniques routinely employed in small molecule NMR, such as HSQC, HMQC, HMBC, COSY, NOESY, TOCSY and similar, can be recorded in a single measurement dramatically reducing the data collection time and increasing sample throughput for basic NMR applications to structure elucidation and verification in synthetic, medicinal and natural product chemistry.